Using Quizlet to Enhance Technical English Vocabulary among Undergraduate Physics Students - S Syamsia; Mahdi Ahmad (Jurnal Langua, 2026)
Mastery of technical English vocabulary is essential for undergraduate physics students because it enables them to comprehend scientific literature, laboratory manuals, and other academic resources written in English. However, many students experience difficulties in learning and retaining technical vocabulary through conventional teaching methods. This study aimed to investigate the effectiveness of Quizlet in enhancing undergraduate physics students' mastery of technical English vocabulary. A quantitative pre-experimental design employing a one-group pre-test–post-test approach was used. The participants were 15 undergraduate students from the Physics Study Program at Institut Sains dan Kependidikan (ISDIK) Kie Raha, selected through purposive sampling. Data were collected using a 30-item multiple-choice technical vocabulary test administered before and after the implementation of Quizlet. The treatment was conducted over three meetings consisting of a pre-test, Quizlet-assisted vocabulary instruction, and a post-test. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-samples t-test. The mean score increased from 62.45 in the pre-test to 75.29 in the post-test. This indicated a statistically significant improvement in students' technical English vocabulary mastery. These findings suggest that Quizlet is an effective digital learning platform for supporting technical vocabulary acquisition in English for Specific Purposes (ESP) courses, particularly for undergraduate physics students.